2021
DOI: 10.29303/alexandria.v2i1.26
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Citra Merek dan Kualitas Produk terhadap Keputusan Pembelian Smartphone Iphone Pada Mahasiswa di Universitas Mataram

Abstract: This study aims to analyze the effect of brand image and product quality on iPhone smartphone purchasing decisions among students at the University of Mataram. This type of research used in this research is associative with a quantitative approach. The sampling technique was determined by purposive sampling method with a total of 100 respondents. The data collection tools used a questionnaire and google form which had been tested for validity and reliability. The data analysis technique used is multiple linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
1
1
5
Order By: Relevance
“…The research gap in product knowledge variables on purchasing decisions was found in the survey conducted by [2][3][4], which found that product knowledge significantly affects the purchasing decisions of non-Muslim customers. This is different from the research conducted by [5], which researched the factors that influence customers' decisions in choosing gold pawn products at Sharia pawnshops, including product knowledge, affordability, trust principles, and service quality, showing that product knowledge has an insignificant relationship with customer purchasing decision behaviour for sharia gold pawn products [26][27][28]. This is in line with research conducted by [6], who found that product knowledge did not have a positive and significant effect on the purchasing decisions of non-Muslim customers.…”
Section: Introductioncontrasting
confidence: 79%
“…The research gap in product knowledge variables on purchasing decisions was found in the survey conducted by [2][3][4], which found that product knowledge significantly affects the purchasing decisions of non-Muslim customers. This is different from the research conducted by [5], which researched the factors that influence customers' decisions in choosing gold pawn products at Sharia pawnshops, including product knowledge, affordability, trust principles, and service quality, showing that product knowledge has an insignificant relationship with customer purchasing decision behaviour for sharia gold pawn products [26][27][28]. This is in line with research conducted by [6], who found that product knowledge did not have a positive and significant effect on the purchasing decisions of non-Muslim customers.…”
Section: Introductioncontrasting
confidence: 79%
“…Citra merek iPhone di bawah Global adalah produk berkualitas tinggi. Portabilitas iPhone dan bentuknya yang unik memudahkan pengguna iPhone untuk mengenali dan mengoperasikan produk iPhone (Lestari & Septiani, 2021). IPhone memiliki OS yang berbeda dari smartphone lainnya, hanya produk Apple yang menggunakan iOS sendiri.…”
Section: Pendahuluanunclassified
“…Previous research has stated that the Country of Manufacture positively influences the perception of quality [5,6,7]. The perception of quality will create confidence in the minds of consumers in a brand product, and the new information thought will determine the purchase [8]. When consumers have a good perception of the country that is the Country of Manufacture, the perceived quality of the product consumers will be better.…”
Section: Introductionmentioning
confidence: 99%